Latent Profile Analysis of Positive Solitude During the Recurrent Outbreak of COVID-19 - Yu, Zhijun; Ye, Baojuan; Hu, Yong; Yang, Qiang (Frontiers in Public Health, 2022)
The current study aimed to identify latent profiles of positive solitude during the recurrent outbreak of COVID-19 among Chinese adults. A total of 902 adults from China completed the questionnaires. We found five different profiles of positive solitude: low positive solitude group, medium-low positive solitude group, quietness positive solitude group, medium-high positive solitude group, and high positive solitude group. Positive and negative affect were significantly different from the five profiles. In addition, gender had different effects on different positive solitude profiles. The results of the study provide a new perspective to understand the positive solitude of Chinese adults during the recurrent outbreak of COVID-19 by using the people-centered approach.